Socioeconomic analysis of hydroponic fodder production in selected areas of Bangladesh: prospects and challenges (SAARC Journal of Agriculture, 2018)
The study was conducted to assess the prospects and challenges of hydroponic fodder production in Bangladesh. A total of 40 farmers were selected purposively from Kishoregonj and Jashore districts as sample for the study. A combination of descriptive, mathematical and statistical techniques was used to analyze the data. The findings of the study revealed that average household and farm size of the farmers were 5.0 persons and 0.48 hectare, respectively. Average annual income of the farmers was Tk. 92312, of which 56.1% income was from farming activities and 43.9% income was from non-farming activities. Majority of the technology adopting farmers (35.8% farmers) were within the late majority group. Profitability analysis showed that net return and benefit cost ratio of hydroponic fodder production were Tk. 5400 per decimal and 1.82, respectively. Farm size, farming experience, training and extension contact had significant impact on farmers’ adoption of hydroponic fodder production technology. Nutritional quality of fodder, high installation cost, medicinal value for human consumption and sensitivity to temperature were the major strength, weakness, opportunity and threat of hydroponic fodder, respectively. This fodder production technology is sustainable from the perspectives of energy use, environmental safety, economic viability and social/political equity. The study recommended that input support (especially seed), motivation, training programmes and extension services by different government and non-government organizations should be properly organized and implemented in town and water logging areas to raise the farmers’ awareness for the adoption of hydroponic fodder production technology.SAARC J. Agri., 16(1): 233-247 (2018)